Design and Performance of a PV-STATCOM for Enhancement of Power Quality in Micro Grid Applications - Lakshman Naik P; K palanisamy (Institute of Advanced Engineering and Science, 2017)
The Green Energy sources (solar, wind) are performing a vigorous role to reach the electrical power demand. Due to the presence of non-linear loads, reactive loads in the distribution system and the injection of wind power into the grid integrated system results power quality issues like current harmonics, voltage fluctuations, reactive power demand etc. This paper mainly investigates the designing and satisfactory performance evaluation of solar farm as PV-STATCOM (Static Synchronous Compensator) for enhancement of power quality in grid tie system by using MATLAB environment (Simulink). The proportional and integral (PI) Controller and Hysteresis Current Controller (HCC) were effectively utilized to inject the desired current from voltage source converter (VSC) based PV-STATCOM at PCC for the mitigation of quality related problems in the proposed test system.